On the rate-distortion regions for interactive source coding - Rey Vega, Leonardo; Piantanida, Pablo; Hero, Alfred O. (Proceedings / IEEE International Symposium on Information Theory, 2015)
The rate-distortion regions of cooperative and interactive source coding is studied and characterized in several important special cases. For the general cooperative and interactive three node source coding problem, we present an improved inner bound with respect to the bound derived in [1]. This inner bound is used to characterize the optimal rate-distortion regions of several special cases of three terminal information sharing protocols.